Introduction – Activist times: temporality and political action in twentieth-century Europe - Paulin-Booth, A; Kerry, M (Taylor and Francis, 2021)
Understandings of time have long formed a fundamental part of political ideologies and served to structure political action. The articles in this special issue of the European Review of History explore different ways in which different groups of activists have drawn on, experienced or projected different understandings of time in Europe in the second half of the twentieth century, often in contexts shaped by substantial upheaval and uncertainty. This introduction outlines the strands of the historiography of time, summarizes some of the underlying themes of the following articles and examines what may be gained from writing time into the history of political activism.